2020
DOI: 10.1089/apc.2019.0165
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structural Marginalization, HIV Stigma, and Mistrust on HIV Prevention and Treatment Among Young Black Latinx Men Who Have Sex with Men and Transgender Women: Perspectives from Youth Service Providers

Abstract: Young black and Latinx men who have sex with men (YBLMSM) and transgender women (YBLTW) are disproportionately impacted by HIV. Structural and social marginalization, the social barriers, and structures that unevenly distribute benefits and burdens to different groups, may contribute to inability for youth to access prevention and treatment care services. Yet, few reports have examined the community and health care experiences of social marginalization among youth service providers who have multiple roles in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…Consistent with RDS recommendations and best practices,[24] RDS implementation was informed by formative research conducted among 18 key informants across the three cities. [18] Once PUSH launched, recruitment followed standard RDS procedures[2] with ongoing recruitment monitoring but added the following modifications for youth, based on prior studies. [13] Eligible and participating youth were offered electronic coupons (e-coupons) with which to recruit peers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with RDS recommendations and best practices,[24] RDS implementation was informed by formative research conducted among 18 key informants across the three cities. [18] Once PUSH launched, recruitment followed standard RDS procedures[2] with ongoing recruitment monitoring but added the following modifications for youth, based on prior studies. [13] Eligible and participating youth were offered electronic coupons (e-coupons) with which to recruit peers.…”
Section: Methodsmentioning
confidence: 99%
“…[16] The violation of these assumptions on population interferences has been explored in reviews and simulation studies,[17] though less is known about individual participant experiences and behaviors that may challenge these assumptions, particularly how the social context of limited disclosure, stigma, and racism experienced in Black and Latinx SGMY (BLSGMY) may impact RDS assumptions. [18]…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of social marginalization on the basis of gender, class, race, sexual identity, poverty, and the intersection of these identities and experiences may contribute to increased vulnerability to HIV infection among Black and Hispanic/Latinx transgender women [ 18 ]. Although several studies have investigated barriers and facilitators to PrEP uptake among transgender women, there is a dearth of research on multilevel barriers to PrEP uptake and adherence specifically among Black and Hispanic/Latinx transgender women.…”
Section: Introductionmentioning
confidence: 99%
“…Focus group participants suggested that the app include the following components: (1) goal planning for ART adherence and substance use treatment, (2) time reminders, (3) adherence reminders, and (4) adherence support (rewards or points for achieving optimal adherence). Findings from key interviews have been described elsewhere [ 54 ]; however, KIs recommended that the study allow for a longer follow-up time (greater than 4 weeks) for coupons to ensure engagement around recruitment, and suggested that the app has rewards for achievement. KIs suggested that the intervention focused on values (health priorities and personal goals), medication initiation and adherence, medical appointments, alcohol or drug use, and sexual health.…”
Section: Methodsmentioning
confidence: 99%